Determinan Pengelolaan Keuangan pada Usaha Mikro Kecil dan Menengah di Kota Langsa - Muhammad Alif Prayuda; Muhammad Salman; Nasrul Kahfi Lubis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to analyze the influence of information technology, business experience, and competence on financial management in Micro, Small, and Medium Enterprises (MSMEs) in Langsa City. A total of 30 respondents, who are MSME entrepreneurs on Teuku Umar Street in Langsa City, were selected as the research sample. The data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination. The research results yielded the following regression equation: Y = 0.888 + 0.318X1 + 0.272 X2 + 0.274 X3. The findings indicate that when information technology, business experience, and competence are considered constant, financial management reaches a value of 0.888. Furthermore, all three independent variables collectively have a significant positive impact on financial management, with an Adjusted R Square value of 0.713. This means that approximately 71.3% of the variation in financial management is explained by the tested variables: information technology, business experience, and competence, while about 28.7% is attributed to other factors not covered in this article. The results of partial hypothesis testing indicate that information technology, business experience, and competence individually have a significant influence on the financial management of MSMEs in Langsa City. The F-test also suggests that all three variables simultaneously have a significant impact on the financial management of MSMEs in Langsa City.